Vārda brīvības ģenēze un preses brīvība Latvijas Republikā starpkaru periodā - Šleiners, Rūdolfs (Latvijas Universitāte, 2012)
Prese starpkaru periodā Latvijas Republikā uzskatāma par nozīmāgāko informācijas aprites līdzekli. Pētāmā periodā Latvijas Republikā preses brīvību un ierobežošanu dažādi normatīvie akti. Valsts iekšējas stāvoklis, normatīvie akti un politisko spēku cīņas par varu ietekmē preses brīvību un plašsaziņas lomu valstī. Šī pētījuma mērķis ir ir izanalizēt vārda brīvības kā vienu no cilvēka pamattiesību, attīstību un vēsturi, kā arī izpētīt vārda un preses brīvību Latvijas Republikā laika posmā no 1918.līdz 1940.gadam, un nobeigumā izvērtēt preses brīvību starpkaru periodā Latvijā. Latvija pasludina sevi par neatkarīgu demokrātisku republiku, bet viena no demokrātijas vērtībām ir tiesības uz vārda un savu, kaut arī iespējams atšķirīgu no vairākuma, viedokļu paušanu. Latvijā starpkaru periodā preses brīvība tika ierobežota. Plašāka atšķirīgo viedokļu apspiešana notiek autoritāra režīma apstākļos.

During the interwar period in Republic of Latvia press is considered as the most important instrument for exchange of information. In this period of time in Republic of Latvia liberty of press and restriction of it is regulated by laws and regulations. The inner situation in country, normative documentation and the race for power of different political forces affect liberty of press and importance of mass media in Latvia. The aim of research is to analyze liberty of speech as one of the fundamental rights of person, its development and history, and to research the liberty of speech and press in Republic of Latvia form 1918 till 1940, and in conclusion evaluate liberty of press during the interwar period in Latvia. Latvia declares itself as independent and democratic republic but one of the values of democracy is the right for freedom of speech and right for expressing own opinion, even if it is different from others. During the interwar period in Latvia liberty of press was often restricted. Wider restrictions of distinctive opinions occur under the regime of authoritarianism.
Genesis of liberty of speech and liberty of press in interwar period in Latvia
Keywords: Juridiskā zinātne